2012
DOI: 10.2466/05.10.pms.114.2.610-626
|View full text |Cite
|
Sign up to set email alerts
|

Application of Regression and Neural Models to Predict Competitive Swimming Performance

Abstract: This research problem was indirectly but closely connected with the optimization of an athlete-selection process, based on predictions viewed as determinants of future successes. The research project involved a group of 249 competitive swimmers (age 12 yr., SD = 0.5) who trained and competed for four years. Measures involving fitness (e.g., lung capacity), strength (e.g., standing long jump), swimming technique (turn, glide, distance per stroke cycle), anthropometric variables (e.g., hand and foot size), as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 18 publications
0
47
0
Order By: Relevance
“…was not superior to the linear regression model in this study. Nevertheless, other studies had found nonlinear models to allow better predictions (Edelmann-Nusser, Hohmann, & Henneberg, 2002;Maszczyk, Zajac, & Ryguła, 2011;Maszczyk, Rocznoik, Waskiewicz, Czuba, Mikolajec, Zajac, & Stanula, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…was not superior to the linear regression model in this study. Nevertheless, other studies had found nonlinear models to allow better predictions (Edelmann-Nusser, Hohmann, & Henneberg, 2002;Maszczyk, Zajac, & Ryguła, 2011;Maszczyk, Rocznoik, Waskiewicz, Czuba, Mikolajec, Zajac, & Stanula, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to comparing linear and nonlinear models with regard to prediction accuracy, the quality of prediction of neural models seems to be similar to that of regression analysis and regression models, potentially even better. This seems to hold true in VO 2 max prediction (Abut, & Akay, 2015;Akay, Zayid, Aktürk, & George, 2011) as well as in performance prediction studies (Edelmann-Nusser, Hohmann, & Henneberg, 2002;Maszczyk, Zajac, & Ryguła, 2011;Maszczyk, Rocznoik, Waskiewicz, Czuba, Mikolajec, Zajac, & Stanula, 2012). Hence, Jäger, Kurz and Müller (2016) assume that nonlinear neural network approaches possibly provide more sophisticated methods for predicting maximal mean speed in a 4x1000 m Field Test which may enhance the accuracy of their linear model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that the ANN is a means of predicting sports results which has a good predictive ability [13,59]. Thus, the ANN enables a coach to model the future level of athletes performance and supports the process of sports selection [34,40,48,52]. For example, Silva et al [52] presented high realistic models of swimming performance prediction based on multilayer perceptron.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the system showed high reliability and high correlation with top experts in the field. While analyzing the literature, it can be also noticed that mathematical models frequently used in sports are artificial neural networks [34,35,40,44,48,50,52,58]. Numerous studies have shown that the ANN is a means of predicting sports results which has a good predictive ability [13,59].…”
Section: Discussionmentioning
confidence: 99%